PENGARUH TERAPI MUSIK KERONCONG LANGGAM JAWA TERHADAP TINGKAT STRES MAHASISWA AKHIR DI UNIVERSITAS SAHID SURAKARTA: PENGARUH TERAPI MUSIK KERONCONG LANGGAM JAWA TERHADAP TINGKAT STRES MAHASISWA AKHIR DI UNIVERSITAS SAHID SURAKARTA - Indriyati, Indriyati (STIKES ADVAITA MEDIKA TABANAN, 2025)
Background: Students study at a university for three to four years and complete their studies by writing a thesis as an admission requirement. The stress experienced by students working on their thesis is academic stress. Academic stress can be addressed with non-pharmacological therapies such as Javanese keroncong music therapy. Objective: To identify the effect of Javanese keroncong music therapy on stress levels in final-semester students at Sahid University, Surakarta. Method: This study used a pre-experimental design with a one-group pretest-posttest. The population was 93 students. The sampling technique used purposive random sampling, with 48 samples. This study was conducted at Sahid University, Surakarta. The DASS21 questionnaire was used as a stress measurement tool. The data were analyzed using paired-sample t-tests. Results: The average stress level before receiving Javanese keroncong music therapy was 13.31. The average stress level after receiving Javanese keroncong music therapy decreased to 10.35. The paired-sample test showed a p-value of 0.001. Conclusion: There was an effect of Javanese keroncong music therapy on stress levels in final-semester students at Sahid University, Surakarta (p-value <0.001).